Immunolocalization and enzymatic functional characterization of the thioredoxin system in Entamoeba histolytica - Arias, Diego Gustavo (2008)
The components of the redox metabolism in Entamoeba histolytica have been recently revisited by Arias et al. (Free Radic. Biol. Med. 42:1496-1505; 2007), after the identification and characterization of a thioredoxin-linked system. The present work deals with studies performed for a better understanding of the localization and identification of different components of the redox machinery present in the parasite. The gene encoding for amoebic thioredoxin 8 was cloned and the recombinant protein typified as having properties similar to those of thioredoxin 41. The ability of these thioredoxins and the specific reductase to assemble a system utilizing NADPH to metabolize hydroperoxides in association with a peroxiredoxin has been kinetically characterized. The peroxiredoxin behaved as a typical 2 cysteine enzyme, exhibiting a ping-pong mechanism with hyperbolic saturation kinetics for thioredoxin 8 (Km = 3.8 μM), thioredoxin 41 (Km = 3.1 μM), and tert-butyl hydroperoxide (Km about 35 μM). Moreover, the tandem system involving thioredoxin reductase and either thioredoxin proved to be operative for reducing low molecular weight disulfides, including putative physiological substrates as cystine and oxidized trypanothione. Thioredoxin reductase and thioredoxin 41 (by association also the functional redox system) have been immunolocalized underlying the plasma membrane in Entamoeba histolytica cells. These findings suggest an important role for the metabolic pathway involving thioredoxin as a redox interchanger, which could be critical for the maintenance and virulence of the parasite when exposed to highly toxic reactive oxygen species.